Chorea Associated with High Titers of Antiphospholipid Antibodies in the Absence of Antiphospholipid Antibody Syndrome - Damoun Safarpour; Sarah Buckingham; Bahman Jabbari (Tremor and Other Hyperkinetic Movements, 2015)
Background: Chorea associated with high titers of antiphospholipid antibodies in the absence of antiphospholipid antibody syndrome has been seldom reported. Case report: An 89-year-old female developed persistent right side chorea associated with high titers of anticardiolipin antibody(antiphospholipid antibosies immunoglobulin(Ig)M, 45 MPL and 112 IgM aCL(MPL) after 3 months) but normal lupus anticoagulants. Her magnetic resonance imaging(MRI) showed no abnormality, but positron emission tomography(PET) demonstrated increased bilateral striatal metabolic activity, more on the left side. Her MRI showed no cause for chorea. The PET scan demonstrated a marked increase in the metabolic activity of the left basal ganglia. Discussion: Her chorea remained unchanged over a 9-month follow-up period. The literature on chorea associated with high titers of antiphospholipid antibodies in the absence of antiphospholipid syndrome is reviewed.